MANAJEMEN ASUHAN KEBIDANAN SEGERA BAYI BARU LAHIR BERKELANJUTAN PADA BAYI NY “M” DENGAN IKTERUS NEONATORUM FISIOLOGIS DI RUMAH SAKIT UMUM BAHAGIA MAKASSAR TAHUN 2021 - Morien Jubella; Ferawati Taherong; Nurfaizah Alza (Jurnal Midwifery, 2022)
Introduction Neonatal jaundice is a clinical condition in infants characterized by a yellow discoloration of the skin and sclera due to excessive accumulation of unconjugated bilirubin. There were about 60% of term infants who experience jaundice in the first week of their age, and about 80% of cases were found in preterm infants. Neontaol jaundice in newborns was a common problem often faced by health workers. The increase level of bilirubin in newborns has been considered to be a normal transition phase. However, the excessive increase of bilirubin in blood can cause a janudice which requires a special treatment. The major purpose of this research was to investigate and conduct a midwifery care management on a newborn of Mrs. “M” with the case of physiological jaundice at Bahagia General Hospital of Makassar. This research was conducted on October 8 to November 21, 2021, and this study was based on the 7 stages of Varney management approach and SOAP documentation procedure. The findings of this study indicated that there were no obstacles found during the process of treatment on the newborn of Mrs. “M”. The treatments and care were conducted for five times for approaximately 1 month. During the process, it was found that the newborn had undergone a jaundice on his skin since october 7, 2021. However, on the third visit, it was apparent that the infant’s condition was better in which the bilirubin level saw a considerable fall. As a result, the treatment of phototheraphy could be discontinued. This study concluded that the newborn’s condition had been good due to the quick and proper treatment and care given to the baby. In this case, the roles of mifwives and health workers are highly significant to deal with patients with the case of neonatal jaundice. Moreover, it is also expected to midwives to give proper understanding and information to the families on the patient so that they could help in the healing process of the baby.